Increased foraging success or competitor avoidance? Diel activity of sympatric large carnivores - Mugerwa, B; du Preez, B; Tallents, L; Loveridge, A; Macdonald, D (Oxford University Press, 2017)
The temporal activity of sympatric carnivores reflects trade-offs between avoidance of competitors and predators, and optimizing foraging success. Closely related species may experience greater interspecific competition for resources due to similar morphologies and ecological requirements. Although the mechanisms by which lions (Panthera leo) and leopards (Panthera pardus) partition diet and habitat have been investigated, the degree to which they avoid each other temporally with possible compromises for foraging success remains less clear. In a wildlife conservancy in Zimbabwe, we used camera trap data to investigate the factors influencing the diel activity of lions and leopards. We modeled diel activity using circular statistics and calculated coefficients of overlap using kernel density functions and non-negative trigonometric sums models. Both leopards and lions were predominately nocturnal, with highly overlapping diel activity. The diel activity of leopards also coincided with that of some prey species, especially common duikers (Sylvicapra grimmia). Therefore, we suggest that leopards may prioritize hunting success and prey acquisition over diel avoidance of dominant competitors like lions.